(untitled) (Indian Journal of Animal Production and Management, 2014)
An experiment was undertaken at ‘Network Project on Swamp Buffalo’, College of Veterinary Science, Assam Agricultural University, Khanapara, Guwahati-22 to study the growth performance of swamp buffalo calves of Assam housed under different roof coverings. Eighteen growing swamp buffalo calves (of either sex) of about 5-6 months of age were selected and housed under three different roof coverings with six calves under each roof covering. The experimental groups, viz. T1, T2 and T3 were allocated to asbestos roof covering, asbestos roof covering with bamboo ceiling, and thatch roof covering respectively. The calves were provided with ad libitum chaffed green forages along with concentrate mixture at the rate of 0.5 per cent of their body weight. No significant difference was observed in growth performance, daily body weight gain, linear body measurements, average daily feed and water intake among the calves of the three groups.